Social banks and the future of sustainable finance - Weber, Olaf, 1965-; Remer, Sven (Routledge international studies in money and banking., 2011)
Social Banks and the Future of Sustainable Finance is the first book to deliver a comprehensive and detailed overview about the past, present and possible future of Social and Sustainable Banking for researchers, students and a professional audience. The authors are experts from research and practice and have bee involved in Social Banking for many years. Thus they combine state-of-the-art expertise with valuable insider knowledge.